Rekonstruksi Konsep Tazkiyatun Nafs Al-Ghazali dalam Bingkai Psikologi Positif: Studi Literasi Upaya Mitigasi Krisis Mental Siswa di Era Digital - Muhammad Ilham Hadinugraha; Mira Mareta; Maimun (Mataram University, 2026)
The mental health crisis of students in the digital era is a pressing issue that cannot be approached solely through a secular clinical psychology approach. This study aims to reconstruct Al-Ghazali's concept of tazkiyatun nafs within the framework of positive psychology as an integrative conceptual framework for mitigating the mental crisis of students in the digital era. The method used is library research with a reconstructive-integrative design, through four analytical techniques: content analysis, comparative analysis, hermeneutic analysis, and conceptual synthesis. Primary sources include Al-Ghazali's works, especially Iḥyāʼ ʿulūm al-dīn, as well as the works of Martin E. P. Seligman as a representation of positive psychology. The results of the study show three main findings. First, Al-Ghazali's concept of tazkiyatun nafs, which encompasses four dimensions of the soul (qalb, rūh, nafs, aql) and three stages of purification (takhalli, taḥallī, tajallī), constitutes a comprehensive psychospiritual development system and corresponds to contemporary neuroscience findings. Second, there are substantial points of convergence between tazkiyatun nafs and Seligman's PERMA model: the takhalli stage corresponds to the Positive Emotions and Engagement elements; the taḥallī stage has a structural parallel with the Character Strengths classification in the VIA framework; and the tajallī stage goes beyond the Meaning element by adding a transcendent dimension. Third, this study formulates an Integrative Conceptual Framework of Tazkiyatun Nafs–Positive Psychology (TKPP) consisting of three layers: spiritual-value foundation, PERMA-based psychological operations, and practical-pedagogical that translates the stages of tazkiyatun nafs into structured educational intervention phases. The TKPP framework is both scientifically grounded and spiritually rooted, relevant as a basis for developing Islamic Religious Education (PAI) curricula, Islamic guidance and counseling, and national education policies in response to students' mental health crises in the digital era.